A Care-Led Recovery From Covid-19: Investing in High-Quality Care to Stimulate And Rebalance The Economy. Issue 1 (3rd April 2021) - De Henau, Jérôme; Himmelweit, Susan
Abstract : The COVID-19 pandemic has both devastated employment prospects, particularly of women, and exposed the longstanding neglect of care systems and poor employment conditions of care workers. Most recovery programs propose to stimulate employment by focusing on investment in construction, ignoring gender equality issues. This paper argues for public investment in high-quality care services and better conditions for care workers to build a more gender-equal caring economy. Using input–output analysis, across selected European Union countries and the United States, the study shows a care-led recovery has superior employment outcomes to investment in construction, even when wages and hours are matched. In particular, matching employment and wages in care to the high levels of Scandinavian countries would raise employment rates by more than 5 percentage points and halve most gender employment gaps, while the net cost of investment in construction that achieved as much would generally be at least twice as high. HIGHLIGHTS Public investment in high-quality care is vital to building a more gender-equal economy. Recovery from COVID-19 requires investment in social, not just physical, infrastructure. A care-led, rather than construction-led, recovery program creates more jobs and reduces gender inequality. More jobs would be created even when employment conditions for care workers are improved. A more caring economy, employing more people in care jobs, is also a greener economy.